PENGARUH AIR REBUSAN DAUN SEMANGGI AIR (Marsilea crenata) TERHADAP PENURUNAN KADAR GLUKOSA DARAH MENCIT (Mus musculus) HIPERGLIKEMIA - Yenny Puspa Rini; Gilang Firmanda; Christina Destri Wiwis Wijayanti; Evy Ratnasari Ekawati (Jurnal SainHealth, 2023)
Hyperglycemia is a marker of diabetes mellitus which is generally caused by damaged pancreatic ? cells which interferes with insulin secretion, causing the amount of blood glucose in the body to be uncontrolled. Marsilea crenata is known to contain several phytochemical compounds such as phenolics, flavonoids and steroids which have a positive effect on treating metabolic disorders. This study aims to determine the effect of Marsilea crenata cooking water on blood glucose levels in Mus musculus. The method used to check blood glucose levels is the POCT method. The results obtained in this study indicate that there is a difference in the average blood glucose examination in the treatment group and the control group. The average blood glucose before treatment was found to be 186.1 mg/dl, while measurements at the 4th and 7th hours after therapy with Marsilea crenata boiled water showed results of 166 mg/dl and 155.2 mg/dl. Statistical tests indicated that there was a significant difference or the effect of giving Marsilea crenata boiled water on decreasing blood glucose levels. Keywords : Marsilea crenata, Mus musculus, Blood glucose level, Hyperglycemia